(untitled) (Global Journal of Human-Social Science, 2018)
The study investigates into the impact of public and private investment on GDP growth in Bangladesh over the period 1980-2016 within ARDL framework. It also enquires into the causal relationship between investment (public and private) and GDP growth using Block Exogeneity Wald Test. The study primarily finds that there exists a significant impact of both public and private investment on GDP growth in the long run. In the short run, public investment does not affect, but private investment has a positive impact on GDP growth. The study also uncovers a bidirectional association between public investment and GDP growth whereas unidirectional relationships from private investment to GDP growth and from public investment to private investment. Consequently, public investment crowds-in private investment. Therefore, increase in public investment is critical to moving to the next level of the country’s growth.